2015
DOI: 10.1016/j.jsbmb.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and regulation of vitamin D hydroxylases and inflammatory genes in prostate stroma and epithelium by 1,25-dihydroxyvitamin D in men with prostate cancer and an in vitro model

Abstract: Previous work on vitamin D in the prostate has focused on the prostatic epithelium, from which prostate cancer arises. Prostatic epithelial cells are surrounded by stroma, which has well-established regulatory control over epithelial proliferation, differentiation, and the inflammatory response. Here we examined the regulation of vitamin D-related genes and inflammatory genes by 1α,25-dihydroxyvitamin D3 (1,25(OH)2D) in laser-capture microdissected prostate tissue from a vitamin D3 clinical trial and in an in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…In addition, nuclear factor kappa-lightchain-enhancer of activated B cells (NF-B) signaling, a major mediator of the immune response, is inhibited in various cancers by 1,25(OH) 2 D 3 by acting on different members of this pathway (304, 455) (FIGURE 7). A suppressed production of inflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-8, IL-17, and TNF-␣ is consistently demonstrated in in vitro and in vivo cancer models (5,162,240,330) (FIGURE 7). In a preclinical SMAD3 knockout model of colitis and colon cancer, Meeker et al (304) showed that a high vitamin D diet decreases NF-B activation in colonic epithelial cells, which is reflected by decreased inflammatory cell infiltrates and reduced expression of proinflammatory cytokines during initiation of carcinogenesis (304).…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 95%
“…In addition, nuclear factor kappa-lightchain-enhancer of activated B cells (NF-B) signaling, a major mediator of the immune response, is inhibited in various cancers by 1,25(OH) 2 D 3 by acting on different members of this pathway (304, 455) (FIGURE 7). A suppressed production of inflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-8, IL-17, and TNF-␣ is consistently demonstrated in in vitro and in vivo cancer models (5,162,240,330) (FIGURE 7). In a preclinical SMAD3 knockout model of colitis and colon cancer, Meeker et al (304) showed that a high vitamin D diet decreases NF-B activation in colonic epithelial cells, which is reflected by decreased inflammatory cell infiltrates and reduced expression of proinflammatory cytokines during initiation of carcinogenesis (304).…”
Section: D) Effects On Inflammation In Cancermentioning
confidence: 95%
“…Primary human stromal (PrS) cells were isolated from radical prostatectomy tissue from PCa patients at the University of Illinois at Chicago Medical Center according to an Institutional Review Board-approved protocol previously described [17]. Briefly, fresh tissue from the peripheral zone was excised with a 5 mm punch from transverse sections of radical prostatectomy specimens by a pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…Prostate stroma from benign areas was collected by LCM as described earlier by Nonn and colleagues [17, 19, 21]. Briefly, two 8 μM formalin-fixed paraffin-embedded sections from each prostatectomy specimen were mounted on RNase-free PEN slides (Leica, Buffalo Grove, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP27B1 expression can be inhibited also by the growth factor independent 1, which represses CYP27B1 transcription by binding to a repressive region in the promoter and recruiting co-repressors with histone deacetylase activity (Dwivedi et al, 2005). A recent study, comparing prostate epithelial and stromal cells from prostate cancer patients, found higher levels of CYP27B1, CYP2R1, and CYP24A1 both in the benign and cancerous epithelia compared with the surrounding stroma (Giangreco et al, 2015).…”
Section: -Hydroxyvitamin D 3 1-alpha Hydroxylase (Cyp27b1) In Cancermentioning
confidence: 99%